Relative Projective Location of Three Bottom Apexes of Petrous Bone on Skull. Issue 6 (September 2016) - Zhang, Qi; Wei, Simeng; Zhang, Jiayi; Cheng, Kailiang; Duan, Haobo; Song, Junxue; Li, Youqiong; Wang, Yiran; Zhou, Shiyu
Abstract : Abstract: The complex anatomy of petrous part of temporal bone makes the craniotomy around this area challenging. To avoid damaging the interior structures of petrous part of temporal bone, the authors used computed tomography to get the projection of the petrous part of temporal bone on skulls, making the external contours of petrous part clear, thus protecting its interior structure as a reference in craniotomy. The objective of this study was to find out the three-dimensional location of 4 points of petrous part of temporal bone. Parameters of 120 patients (240 observations) between 25 and 65 years who were free of abnormalities and pathological changes in temporal bone were measured on high-resolution spiral multiple slice computed tomographic multiple planar reconstruction images that were parallel to the base plane. The data were analyzed by SPSS, statistical software with the comparison between sides and sexes. The authors found the accurate locations that 4 points of petrous part of temporal bone with mastoidale as the origin. Then the authors connect the 3 vertexes of underside and the petrous apex and lengthen it until intersect with skulls to get the external landmarks. In the end, the authors get the safe range that can be applied to the clinical surgery.